Edukasi Gizi dalam Upaya Pencegahan Osteoporosis pada Lansia di Kota Padang - Syahrial Syahrial; Helmizar Helmizar; Salma Nur Fitri (Warta Pengabdian Andalas, 2023)
Increasing the degree of health means that life expectancy will also increase, and the number of older people will also increase. The consequence of increasing life expectancy is the emergence of disease problems due to old age, one of which is osteoporosis. This activity aimed to determine the health status of the elderly by conducting health checks and providing nutrition education to prevent osteoporosis in Padang City. The service was held in Korong Gadang Elderly Posyandu in April - September 2021. The community service included health checks by measuring blood pressure, measuring the nutritional status of the elderly, as well as nutrition education to prevent osteoporosis in the elderly, especially for menopausal women. This activity received a positive response from the community, and it was agreed that ongoing activities would be carried out in the form of routine health checks and counselling for the older people in the area.